Concrete and method for repairing existing concrete structure
Patent Information
- Application Number
- JP2023124952
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0011】 本発明によれば、曲げ靭性係数を向上させることができるため、ひび割れ、浮きや剥がれを抑制できる。
Smart Images

Figure 2025021185000005 
Figure 2025021185000001 
Figure 2025021185000002
Abstract
Description
[Technical field]
[0001] The present invention relates to rapid-hardening concrete and a method for repairing an existing concrete structure. [Background technology]
[0002] When a concrete deck on a road bridge or the like is damaged by vehicle traffic or other factors, the damaged area is repaired. In general, when repairing a damaged concrete deck, the asphalt laid on the top surface of the concrete deck is removed, the damaged existing concrete is cut away, and new concrete is poured and allowed to harden. The repair is then completed by applying asphalt paving again.
[0003] Repairs to concrete decks require vehicle closures, so they can be completed quickly, such as at night, and rapid-hardening concrete is used, which can develop a desired strength within a few hours of pouring. For example, ultra-fast-hardening concrete, which is made by mixing aggregate with ultra-fast-hardening cement, has a compressive strength of 24.0 (N / mm) at three hours. 2 ) or more, and as a result, repairs can be completed in a short period of time.
[0004] However, conventional ultra-fast hardening concrete has a compressive strength of 60 (N / mm 2 ), and the static elastic modulus is 40 (kN / mm 2 On the other hand, the compressive strength of existing concrete decks, such as road bridges, is about 24 to 30 (N / mm 2 ), and the static elastic modulus is 25 to 30 (kN / mm 2) for this reason. When a deck is repaired using conventional ultra-fast hardening concrete, the compressive strength and static elastic modulus of the repaired area will be significantly different from those of the existing concrete deck. As a result, when repeated vehicle loads act on the repaired area after traffic is allowed to resume, stress will be concentrated at the boundary between the repaired area and the existing concrete deck, and deterioration such as cracks may occur at this boundary. For this reason, concrete used as a repair material needs to have fast hardening properties and also needs to have a low long-term static elastic modulus.
[0005] Therefore, Patent Document 1 discloses a concrete having rapid hardening properties, which contains a rapid hardening binder containing cement, fine aggregate, coarse aggregate, latex, elastic aggregate, and a retarder. According to the technology disclosed in Patent Document 1, it is said that the concrete has rapid hardening properties and can reduce the static elastic modulus over a long period of time. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-233696 A Summary of the Invention [Problem to be solved by the invention]
[0007] The technology disclosed in Patent Document 1 can suppress cracks from the boundary with the existing concrete deck by reducing the static elastic modulus over a long period of time. However, if the flexural toughness of the rapid-hardening concrete itself is low, there is a risk that the rapid-hardening concrete itself will crack, float, or peel. Therefore, there is a strong demand for rapid-hardening concrete that can suppress cracks, float, and peel during service.
[0008] The present invention has been devised in consideration of the above-mentioned problems, and an object of the present invention is to provide a rapid-hardening concrete that can suppress cracking, lifting, and peeling, and a method for repairing existing concrete structures. [Means for solving the problem]
[0009] The concrete according to the first invention is a rapid-hardening concrete containing a rapid-hardening binder containing cement, fine aggregate containing elastic aggregate, coarse aggregate, latex, a setting retarder, and steel fibers, the content of the latex being 5.0% by weight or more and 14.0% by weight or less in terms of solid content relative to the weight of the rapid-hardening binder, the content of the elastic aggregate being 1.5% by volume or more and 5.0% by volume or less relative to the total volume, the elastic aggregate having a static elastic modulus of 1 to 10 MPa and a maximum particle size of 5.0 mm or less, and the content of the steel fibers being 150% by weight or more and 250% by weight or less relative to the weight of the latex converted into solid content.
[0010] A method for repairing an existing concrete structure according to the second invention is characterized in that the existing concrete structure is repaired by using the concrete of the first invention. Effect of the Invention
[0011] According to the present invention, the flexural toughness coefficient can be improved, so that cracks, lifting, and peeling can be suppressed. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a graph showing the grading curve of elastic aggregate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the concrete to which the present invention is applied will be described in detail.
[0014] The concrete to which the present invention is applied contains a fast-hardening binder containing cement, fine aggregate containing elastic aggregate, coarse aggregate, latex, a retarder, and steel fibers, the latex content is 3.0% to 14.0% by weight in terms of solid content based on the weight of the fast-hardening binder, the elastic aggregate content is 1.5% to 5.0% by volume based on the total volume, and the steel fiber content is 150% to 250% by weight based on the weight of the latex converted into solid content.
[0015] The components used in the concrete to which the present invention is applied will be described below.
[0016] <Fast hardening binder> The fast-setting binder contains cement and a fast-setting admixture.
[0017] <Cement> The cement may be, for example, Portland cement of normal, early strength, extra early strength, moderate heat, low heat, low sulfate, etc. The cement may be any of various blended cements in which Portland cement is mixed with fly ash, blast furnace slag, silica fume, limestone powder, etc. One or more types of cement may be used as appropriate.
[0018] <Fast hardening admixture> The rapid-hardening admixture imparts rapid hardening to concrete. Examples of the rapid-hardening admixture include those mainly composed of one or more substances selected from the group consisting of calcium aluminate, sodium aluminate, alum containing calcined alum, activated alumina, aluminum hydroxide, aluminum sulfate, calcium nitrite, calcium nitrate, etc. Particularly preferred rapid-hardening admixtures are those mainly composed of calcium aluminate. The rapid-hardening admixture is preferably in powder form.
[0019] Calcium aluminate-based fast-setting admixtures are classified as C3A, C2A, and C, where CaO is C, Al2O3 is A, Na2O is N, and Fe2O3 is F. 12Calcium aluminate with a mineral composition indicated as A7, C5A3, CA, C3A5 or CA2, calcium aluminoferrite indicated as C2AF or C4AF, calcium aluminate with halogen as a solid solution or as a substitute, C3A3·CaF2 or C 11 These include calcium haloaluminates, including calcium fluoroaluminate, designated as A7·CaF2, calcium sodium aluminate, designated as C8NA3 or C3N2A5, calcium lithium aluminate, calcium sulfoaluminate such as auin (3CaO·3Al2O3·CaSO4), and those in which SiO2, K2O, Fe2O3, TiO2, etc. are dissolved or combined.
[0020] In addition to the above-mentioned rapid hardening substances, sulfates, carbonates, nitrates, hydroxides, etc. are appropriately used in combination with the rapid hardening admixture. When sulfates such as sodium sulfate, potassium sulfate, and calcium sulfate are used, they are preferred because they enhance the strength development.
[0021] The content of the fast-setting admixture is preferably 20.0% by weight or more and 40.0% by weight or less based on the weight of the fast-setting binder. If the content of the fast-setting admixture is less than 20.0% by weight based on the weight of the fast-setting binder, the fast-setting properties cannot be exhibited. If the content of the fast-setting admixture is more than 40.0% by weight based on the weight of the fast-setting binder, the specified pot life cannot be ensured.
[0022] As a substitute for the rapid-setting binder containing cement and a rapid-setting admixture, ultra rapid-setting cement or alumina cement may be used.
[0023] <Fine aggregate> The fine aggregate includes normal fine aggregate used in the production of general concrete and elastic aggregate. Examples of normal fine aggregate include river sand, sea sand, crushed sand, artificial fine aggregate, slag fine aggregate, recycled fine aggregate, and silica sand.
[0024] <Elastic aggregate> The elastic aggregate is, for example, a rubber elastic body having a static elastic modulus of about 1 to 10 MPa and has a predetermined elongation. For example, the elastic aggregate has a maximum particle size of 5.0 mm or less. The elastic aggregate has a predetermined static elastic modulus and is excellent in quality stability. By containing the elastic aggregate, it is possible to secure a predetermined volume in the concrete and reduce costs. In addition, the elastic aggregate may be rubber chips or powder made by shredding industrial waste rubber into a predetermined size, which makes it possible to significantly reduce costs. Furthermore, in addition to the rubber elastic body, the elastic aggregate may be resin, other elastomers, cork, etc.
[0025] Examples of the rubber elastic body include those mainly composed of one or more of SBR (styrene butadiene rubber), BR (butadiene rubber), NR (natural rubber), MBR (methyl methacrylate butadiene rubber), VP (2-vinylpyridine styrene butadiene), NBR (acrylonitrile butadiene), CR (chloroprene rubber), IR (isoprene rubber), etc. There are no particular restrictions on the resin as long as it has elasticity, but it is preferable to use a urethane-based resin.
[0026] If the content of elastic aggregate is less than 1.5% by volume relative to the total volume of concrete, the long-term static modulus of elasticity of concrete cannot be reduced. Also, if the content of elastic aggregate is more than 5.0% by volume relative to the total volume of concrete, rapid hardening properties cannot be fully exhibited. Therefore, the content of elastic aggregate is set to 1.5% to 5.0% by volume relative to the total volume of concrete. More preferably, the content of elastic aggregate is set to 3.0% to 5.0% by volume relative to the total volume of concrete, which allows for a further reduction in the long-term static modulus of elasticity.
[0027] <Coarse aggregate> The coarse aggregate used may be any coarse aggregate commonly used in the production of concrete, such as river gravel, land gravel, crushed stone, artificial coarse aggregate, slag coarse aggregate, recycled coarse aggregate, etc.
[0028] <Latex> Latex is an emulsion in which a polymer is dispersed in water in a colloidal state by the action of an emulsifier. Examples of latex include latexes that are mainly composed of one or more of SBR (styrene butadiene rubber) latex, BR (butadiene rubber) latex, NR (natural rubber) latex, MBR (methyl methacrylate butadiene rubber) latex, VP (2-vinylpyridine styrene butadiene) latex, NBR (acrylonitrile butadiene) latex, CR (chloroprene rubber) latex, and IR (isoprene rubber) latex. As the latex, SBR latex is preferred.
[0029] If the content of latex is less than 5.0% by weight in terms of solid content relative to the weight of the fast-hardening binder, the flexural toughness of the concrete cannot be improved. Also, if the content of latex is more than 14.0% by weight in terms of solid content relative to the weight of the fast-hardening binder, material separation occurs in the concrete, and the concrete cannot be molded. Therefore, the content of latex is set to 5.0% by weight or more and 14.0% by weight or less in terms of solid content relative to the weight of the fast-hardening binder. More preferably, the content of latex is set to 5.0% by weight or more and 10.0% by weight or less in terms of solid content relative to the weight of the fast-hardening binder, thereby enabling further improvement of the fast-hardening property.
[0030] <Water> The water used may be the same as that used in the production of ordinary concrete, such as tap water.
[0031] The water content is preferably 15.0% to 35.0% by weight based on the weight of the fast-hardening binder. If the water content is less than 15.0% by weight based on the weight of the fast-hardening binder, sufficient mixing is not possible. If the water content is more than 35.0% by weight based on the weight of the fast-hardening binder, separation of the materials occurs and the material cannot be cast into concrete.
[0032] <Set retarder> The setting retarder is for ensuring a predetermined pot life of, for example, about 20 minutes or more. The setting retarder may be in the form of a powder or liquid. Examples of setting retarders include those containing one or more selected from the group consisting of organic acids such as oxycarboxylic acids such as citric acid, gluconic acid, malic acid, and tartaric acid, or their salts, boric acid, borates such as sodium borate, phosphates, inorganic salts such as sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate, and sugars. Among these, those containing one or more selected from the group consisting of citric acid, citrates, tartaric acid, tartrates, and alkali metal carbonates are preferred.
[0033] The content of the setting retarder is preferably 0.05% by weight or more and 1.0% by weight or less based on the weight of the fast-hardening binder. If the content of the setting retarder is less than 0.05% by weight based on the weight of the fast-hardening binder, the specified pot life cannot be ensured. If the content of the setting retarder is more than 1.0% by weight based on the weight of the fast-hardening binder, the setting time becomes too slow and the fast-hardening properties cannot be achieved.
[0034] The concrete to which the present invention is applied may contain various additives (agents) as necessary, provided that the characteristics of the present invention are not impaired. Examples of additives (agents) include water reducing agents, AE water reducing agents, high performance water reducing agents, high performance AE water reducing agents, cement dispersants such as flow agents, strength promoters, re-emulsified powdered resins, foaming agents, foaming agents, waterproofing agents, rust inhibitors, shrinkage reducing agents, thickeners, pigments, water repellents, efflorescence prevention agents, and defoamers.
[0035] <Steel fiber> The steel fibers may be commercially available as steel fibers for steel fiber reinforced concrete, so-called SFRC (Steel Fiber Reinforced Concrete). Examples of the steel fiber material include ordinary steel fibers made of rolled steel, rolled steel plate, steel strip, iron wire, or equivalent or higher steel materials, and stainless steel fibers made of stainless steel bars, rolled stainless steel plates, steel strips, stainless steel wires, or equivalent or higher stainless steel materials. Examples of the shape of the steel fiber include hook type, straight type, and wave type, and the hook type is preferable from the viewpoint of improving the adhesion between the concrete and the steel fiber and improving the toughness. The cross section of the steel fiber may be rectangular, circular, or other than rectangular or circular. The steel fibers may be bundled or not bundled. The length of the steel fiber is preferably 20 mm to 40 mm, more preferably 25 mm to 35 mm. The diameter of the steel fiber is preferably 0.3 mm to 0.9 mm, more preferably 0.35 to 0.7 mm. The tensile strength of steel fibre is 600N / mm 2 More than 1200N / mm 2 The above are preferred. The higher the tensile strength of the steel fibres, the better the flexural toughness of the concrete, so it is more preferred to use steel fibres with high tensile strength.
[0036] The steel fiber content is 150% by weight or more and 250% by weight or less based on the weight of the latex solid content. This can improve the flexural toughness of the concrete. On the other hand, if the steel fiber content is less than 150% by weight based on the weight of the latex solid content, the effect of improving the flexural toughness of the concrete is low. On the other hand, if the steel fiber content is more than 250% by weight based on the weight of the latex solid content, the effect of improving the flexural toughness of the concrete is low.
[0037] The concrete to which the present invention is applied can be used to repair existing concrete structures. The concrete to which the present invention is applied can be used as a cross-section repair material for existing concrete slabs. The concrete to which the present invention is applied can be used as a concrete paving material laid on the top surface of an existing concrete slab. The concrete to which the present invention is applied can be used as joint concrete for bridges. The concrete to which the present invention is applied can be used as a filler material between precast slabs.
[0038] In the method for repairing an existing concrete structure to which the present invention is applied, the existing concrete structure is repaired using concrete to which the present invention is applied. In the following, the existing concrete structure will be described as a concrete deck of a bridge.
[0039] In the repair method of an existing concrete structure to which the present invention is applied, the asphalt covering the existing concrete slab is removed as necessary. Then, the damaged existing concrete slab is cut and ground, and concrete to which the present invention is applied is poured into the cut portion and allowed to harden. After that, asphalt is laid as necessary.
[0040] The concrete to which the present invention is applied and used to repair an existing concrete deck slab has rapid hardening properties because it contains a rapid hardening binder.
[0041] According to this embodiment, the content of steel fiber is 150% by weight or more and 250% by weight or less based on the weight of the solid content of the latex. This improves the flexural toughness of the concrete. This makes it possible to suppress cracking, lifting, and peeling of the concrete caused by the action of external force. EXAMPLES
[0042] Hereinafter, concrete to which the present invention is applied will be specifically described with reference to examples, comparative examples, and reference examples.
[0043] The materials used in the following Examples, Comparative Examples and Reference Examples are as follows. Fast-hardening binder: Contains cement and fast-hardening admixture Cement: Ordinary Portland cement, manufactured by Taiheiyo Cement Corporation. Density: 3.16 g / cm 3 Fast-hardening admixture: Calcium aluminate-based fast-setting admixture Density: 2.93g / cm 3 Fine aggregate: Contains crushed sand and elastic aggregate Crushed sand: Granite crushed sand Density: 2.58g / cm 3 Elastic aggregate: Rubber chips containing NR and SBR Density: 1.2g / cm 3 Coarse aggregate: Crushed hard sandstone Density: 2.72g / cm 3 Latex: SBR type, solid content 45%, density: 1.0, average particle size: 0.2 μm Retarder: Hydroxycarboxylic acid powder Density: 1.67g / cm 3 Steel fiber: Bekaert Dramix 3D-45 / 30BG, length: 30 mm, diameter: 0.62 mm, density: 7.87 g / cm 3 Water: Tap water
[0044] Figure 1 shows the grading curve of the elastic aggregate. The grading of the elastic aggregate was measured in accordance with JIS A1102. Table 1 shows the relationship between the sieve size, the residual rate, and the passing rate in the measurement of the grading of the elastic aggregate. The coarse aggregate ratio of the elastic aggregate was 3.68.
[0045] [Table 1]
[0046] The hardness of the elastic aggregate is shown in Table 2. The hardness was measured in accordance with JIS K 6253-3.
[0047] [Table 2]
[0048] Table 3 shows the concrete mixes of the Examples, Comparative Examples, and Reference Examples. In Table 3, "W" indicates the weight of water, "L" indicates the weight of latex converted into solid content, "B" indicates the weight of the fast-hardening binder, "S" indicates the weight of fine aggregate, "G" indicates the weight of coarse aggregate, "SF" indicates the weight of steel fiber, and "Re" indicates the weight of the retarder. As shown in Table 3, in each mix, the weights of the fast-hardening binder, fine aggregate, and coarse aggregate were fixed, and the contents of latex and steel fiber were variables. In each mix, the air volume was set to 20 liters. The weight of the fast-hardening binder "B" was 453 kg, which is the sum of the weight of cement 306 kg and the weight of the fast-hardening admixture 147 kg. The weight of the fine aggregate "S" was 717 kg, which is the sum of the weight of crushed sand 666 kg and the weight of elastic aggregate 51 kg. In Table 3, "W / B" indicates the ratio of the weight of water to the weight of the fast-hardening binder. "L / B" indicates the ratio of the weight of latex, converted into solid content, to the weight of the fast-hardening binder. "Elastic aggregate / total volume" indicates the ratio of the volume of elastic aggregate to the total volume of concrete. "SF / L" indicates the ratio of the weight of steel fiber to the weight of latex, converted into solid content. Note that retarders are included as an external percentage and are not included in the total volume of concrete. The total volume of concrete includes 20 liters of air.
[0049] The reference example was a concrete mix that did not contain latex, and the mix was set so that the steel fiber content was the same as that of the working example and the comparative example.
[0050] [Table 3]
[0051] Concrete was prepared according to the mix proportions shown in Table 3. The concrete was prepared by putting all the materials to be used into a concrete mixer and mixing for 3 minutes.
[0052] In the examples, comparative examples, and reference examples, the flexural toughness coefficient was measured in accordance with JSCE G 552 "Test method for flexural strength and flexural toughness of steel fiber reinforced concrete."
[0053] Table 4 shows the results of the flexural toughness coefficient and the flexural toughness coefficient ratio. Here, the flexural toughness coefficient of the Example or the Comparative Example relative to the flexural toughness coefficient of the Reference Example is defined as the flexural toughness coefficient ratio. In this study, the degree to which the flexural toughness coefficient of the test specimens containing latex (Examples 1 to 9, Comparative Examples 1 to 4) was improved relative to the flexural toughness coefficient of the test specimens not containing latex (Reference Examples 1 to 13) was evaluated based on the flexural toughness coefficient ratio.
[0054] [Table 4]
[0055] In Examples 1 to 9, the content of latex is 5.0% by weight or more and 14.0% by weight or less in terms of solid content relative to the weight of the fast-hardening binder, the content of elastic aggregate is 1.5% by volume or more and 5.0% by volume or less relative to the total volume of concrete, and the content of steel fiber is 150% by weight or more and 250% by weight or less in terms of the weight of latex in terms of solid content. As a result, the flexural toughness coefficient ratios of Examples 1 to 9 were 1.19 to 1.35. That is, the flexural toughness coefficients of Examples 1 to 9 containing latex and steel fiber were improved compared to the flexural toughness coefficients of Reference Examples 1 to 9 not containing latex. Therefore, the fast-hardening properties are obtained and cracks, lifting, and peeling can be suppressed. In particular, in Examples 5 and 6, the content of latex is 10.0% by weight in terms of solid content relative to the weight of the fast-hardening binder. In Examples 5 and 6, the flexural toughness coefficient ratios were 1.3 or more, and the flexural toughness coefficients were greatly improved.
[0056] In Comparative Example 1, the content of steel fibers was 50% by weight based on the weight of the solid content of the latex. In this case, the effect of improving the bending toughness coefficient was low compared to Reference Example 10 which did not contain latex.
[0057] In Comparative Example 2, the content of steel fibers was 350% by weight based on the weight of the solid content of the latex. In this case, the effect of improving the bending toughness coefficient was low compared to Reference Example 11 which did not contain latex.
[0058] In Comparative Example 3, the content of latex was 3.0% by weight in terms of solid content relative to the weight of the fast-hardening binder. In this case, the flexural toughness coefficient was approximately the same as that of Reference Example 12, which did not contain latex.
[0059] In Comparative Example 4, the content of latex was 17.5% by weight in terms of solid content relative to the weight of the fast-hardening binder. In this case, it was impossible to mold a test specimen due to material separation.
Claims
1. A rapid hardening concrete, The concrete mixture contains a fast-hardening binder containing cement, fine aggregate containing elastic aggregate, coarse aggregate, latex, a retarder, and steel fibers. The content of the latex is 5.0% by weight or more and 14.0% by weight or less in terms of solid content based on the weight of the fast-hardening binder, The content of the elastic aggregate is 1.5% by volume or more and 5.0% by volume or less with respect to the total volume, The elastic aggregate has a static elastic modulus of 1 to 10 MPa and a maximum particle size of 5.0 mm or less; The content of the steel fibers is 150% by weight or more and 250% by weight or less based on the weight of the solid content of the latex. Concrete characterized by:
2. Repairing an existing concrete structure using the concrete according to claim 1. A method for repairing an existing concrete structure, comprising:
Citation Information
Patent Citations
JP2020-233696A